1952
DOI: 10.1021/ac60069a037
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Stability of Aqueous Potassium Ferrate(VI) Solutions

Abstract: ECEST interest in the use of ferrate compounds as strong ' oxidizing agents prompted an investigation of some factors influencing the stability of potassium ferrate solutions. In a study of the st,ahility of ferrate ions in aqueous solutions, Schreyer and Ockerman (2j found that the more dilute solutions of ferrate are more stable. They found also that some added salts, after increasing the initial deconiposition rate of ferrate solutions, apparently staliiljze the remainder; and that ferrate ions are more sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 3 publications
1
51
0
Order By: Relevance
“…The decomposition rate of potassium ferrate(VI) highly depends on the pH of the aquatic environment. Generally, with reducing pH values, the stability of potassium ferrate(VI) reduces (Wanger et al, 1952). For example, 49% of potassium (7) 19.20 0 AE 0 0 (0)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decomposition rate of potassium ferrate(VI) highly depends on the pH of the aquatic environment. Generally, with reducing pH values, the stability of potassium ferrate(VI) reduces (Wanger et al, 1952). For example, 49% of potassium (7) 19.20 0 AE 0 0 (0)…”
Section: Discussionmentioning
confidence: 99%
“…Temperature should be considered in the applications, because temperature in the field also influences the decomposition rate of ferrate(VI) solution (Wanger et al, 1952;Johnson and Sharma, 1999). For a given 2-h test period, potassium ferrate(VI) solution (initial concentration: 0.01 M) was reduced by 10% at 25 8C and almost unchanged at 0.5 8C (Wanger et al, 1952).…”
Section: Discussionmentioning
confidence: 99%
“…The ferrate solution prepared with buffer solution at pH 8 was more stable than that prepared at pH 7 [31]; 49% of the original potassium ferrate remained after 8 h when the pH was 7, and 71.4% of that remained after 10 h when the pH was 8. Temperature dependence data showed that ferrate(VI) solutions are relatively stable at low temperature conditions (0.5 0 C) [32]. The 0.01 M solution of Fe(VI) was reduced by 10% at a constant temperature of 25 0 C and almost unchanged at 0.5 0 C for a period of 2 h.…”
Section: Stability and Speciation Of Ferrate(vi)mentioning
confidence: 95%
“…This oxidant is considerably stable in strongly alkaline solution around pH 10, whereas it decomposes spontaneously at a very rapid rate in acidic or neutral solution. 18,19 In an aqueous solution three types of ferrate coexist in equilibrium: non-protonated ( …”
mentioning
confidence: 99%